Cultural Heritage Literacy of The Students of Information Management: The Case of Hacettepe University - Öztemiz, Semanur (Information World, 2020)
Protection of cultural heritage products in a sustainable manner requires the information concerning those products to be accessible, usable and shareable. Even the skills of cultural heritage literacy, which form the basis of this process, are important for everyone, these skills are much more necessary for information professionals who have the responsibility to provide service in the area of cultural heritage. Evaluating cultural heritage literacy skills of information professional candidates, carries a great importance in order to understand whether they have adequate qualification while serving as a professional and to determine necessary training subjects they need. In this study, it is aimed to determine the current situation of the students of Hacettepe University Department of Information Management on cultural heritage literacy. For this purpose, a questionnaire of 28-question was sent to 356 undergraduate students via e-mail in 2018-2019 Spring Semester. 142 students answered to whole questionnaire. The data were analysed using descriptive statistics and a chi-square test. Findings showed that most of the participants have efficient cultural heritage literacy skills, and they have dominant competences in recognizing their information necessities regarding cultural heritage and sharing their cultural heritage information. It is considered beneficial especially for information professionals who have functions of protecting and transferring cultural heritage to the next generations, to add courses or course contents directly related to cultural heritage literacy to undergraduate programs of Information and Record Management Departments.
Keywords: Cultural heritage; cultural heritage literacy skills; Information Management students